1989
DOI: 10.1159/000132726
|View full text |Cite
|
Sign up to set email alerts
|

Molecular definition of de novo and genetically transmitted WAGR-associated rearrangements of 11p13

Abstract: We describe a family in whom the phenotypically normal father carries a balanced insertional translocation, ins(14;11)(q23;p12p14). This individual fathered three mentally retarded children, two with a del(11)(p13) and one with a dup(11)(p13). Two other cases of a de novo del(11)(p13) are also described. All four del(11)(pl3) cases presented with WAGR, a complex syndrome associated with a predisposition to Wilms’ tumor (WT), aniridia (A), genitourinary abnormalities (G), and mental retardation (R). Using an ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
15
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 14 publications
4
15
0
Order By: Relevance
“…Our patient, however, does not show these clinical features. Lavedan et al (1989) also reported a patient (LEV4) with a duplication of 11 pi 3 who had no obvious dysmorphic signs or malformations but did have mild mental retardation. The milder phenotypic features of our patient, as well as those of LEV4.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our patient, however, does not show these clinical features. Lavedan et al (1989) also reported a patient (LEV4) with a duplication of 11 pi 3 who had no obvious dysmorphic signs or malformations but did have mild mental retardation. The milder phenotypic features of our patient, as well as those of LEV4.…”
Section: Discussionmentioning
confidence: 98%
“…Southern hybridization, using DNA probes presumed to be located within the rearranged region, has occa sionally yielded useful data (Lavedan et al, 1989) but does not provide information on the physical location of the probe, as does in situ hybridization. We illustrate here the application of in situ hybridization with a biotinylated single-copy DNA probe combined with Southern blot analysis to identify the origin of an abnormal chromosome 11 in a patient with mild mental retardation but without remarkable dysmorphic signs.…”
mentioning
confidence: 99%
“…Complete or partial trisomy of 11p, including 11p13, was described before in 11 cases [Aleck et al, 1985;Falk et al, 1973;Fryns et al, 1981Fryns et al, , 1985Lavedan et al, 1989;Ogur et al, 1988;Palmer et al, 1976;Palutke et al, 1980;Sanchez et al, 1974;Speleman et al, 1991;Strobel et al, 1980]. In two of these cases, the duplication was de novo.…”
Section: Discussionmentioning
confidence: 84%
“…They all involved matemal inheritance except one case of insenion (Lavedan et al, 1989). Altogether these observations soggest that the asymptomatic carriers presented with an apparently balanced rearrangement.…”
mentioning
confidence: 73%